2019
DOI: 10.1002/asia.201900625
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Heating Outperforms Conventional Heating for a Thermal Reaction that Produces a Thermally Labile Product: Observations Consistent with Selective Microwave Heating

Abstract: Microwave( MW) heatingi sm ore effective than conventional (CONV)h eating for promoting ah igh-temperature oxidative cycloisomerization reaction that was previously reported as ak ey step in at otal synthesis of the naturalp roduct illudinine.T he thermal reaction pathway as envisioned is an inverse electron-demand dehydro-Diels-Alder reaction with in situ oxidation to generate as ubstituted isoquinoline, which itself is unstablet ot he reaction conditions. Observed reaction yields were higher at am easured bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…We later reexamined this reaction systematically, focusing on temperature, time, and heating mode (MW v CONV). 30 Yields were consistently highest at 200 °C and 24 h compared with temperatures and times above and below these values. It was also found that solutions of the substrate heat more efficiently in the microwave than solutions of the product (faster and to higher temperature at constant MW power) and that isolated yields of product were consistently higher under MW compared to CONV heating, despite essentially identical temperature profiles and other reaction variables.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…We later reexamined this reaction systematically, focusing on temperature, time, and heating mode (MW v CONV). 30 Yields were consistently highest at 200 °C and 24 h compared with temperatures and times above and below these values. It was also found that solutions of the substrate heat more efficiently in the microwave than solutions of the product (faster and to higher temperature at constant MW power) and that isolated yields of product were consistently higher under MW compared to CONV heating, despite essentially identical temperature profiles and other reaction variables.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…First-Generation Synthesis. 29,30 The synthesis of illudinine as previously reported is outlined in Scheme 4. The hydroxycycloalkenyl triflate (6) needed for fragmentation/olefination can be reached in two steps from dimedone (cf.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notable illudalane syntheses include that of illudalic acid and illudinine by Woodward and Hoye in 1977, that of illudinine by Teske and Deiters in 2008, that of alcyopterosin A by Sato in 2002 and by Iglesias in 2006, and those of several other alcyopterosins by Witulski in 2010 . We reported syntheses of alcyopterosin A in 2016 and illudinine in 2017, with the latter synthesis updated in 2020 . Eight additional publications on the synthesis of illudalane sesquiterpenes have appeared since the beginning of 2018, as these targets increasingly attract attention for natural product synthesis.…”
mentioning
confidence: 99%